INDIA-US STRATEGIC PARTNERSHIP SEBAGAI UPAYA INDIA MENGAMANKAN WILAYAH PERBATASAN DENGAN TIONGKOK - Vania Bunga Widhianingsih; Reni Windiani; Fendy Eko Wahyudi (Journal of International Relations, 2022)
China has been India’s major trading partner for five consecutive years since 2013. India and China have formed cooperation agreements in several sectors such as trade, investment, and infrastructure. However, the bilateral relation between India and China has been fractured since the border conflict re-occurred in 2017. The Border conflict make India wants to reduce economic cooperation with China. In the end, India's perception of the cooperation has led India to make a new strategy to increase independence and reduce China's economic dominance. India's effort to reduce cooperation with China is supported by increasing the economic cooperation with the United States through the "India-US Strategic Partnership." The theory used to answer the formulation of the problem is the Theory of Rational Choice, proposed by Charles W. Kegley and Shannon L. Balton in 2008 and using qualitative methods. The results of this study indicate that India’s decision to increase cooperation with United States is supported by several factors including security and economic factors.